Environmental regulation, technology adoption and structural transformation: evidence from Brazilian sugarcane industry - Lima Filho, Francisco Luis (2015)
We estimate the effects of the adoption of mechanized agriculture led by a new environmental regulation on structural change of local labor markets within a large emerging country, Brazil. In 2002, the state of São Paulo passed a law outlying the timeline to end sugarcane pre-harvest burning in the state. The environmental law led to the fast adoption of mechanized harvest. We investigate if the labor intensity of sugarcane production decreases; and, if so, if it leads to structural changes in the labor market. We use satellite data containing the type of sugarcane harvesting -- manual or mechanic harvest -- paired with official labor market data.%, also geomorphometric data base for our instrumental variable correction. We find suggestive evidence that mechanization of the field led to an increase in utilization of formal workers and a reduction in formal labor intensity in the sugarcane sector. This is partially compensated by an increase in the share of workers in other agricultural crops and in the construction and services sector. Although we find a reduction in employment in the manufacturing sector, the demand generated by the new agro-industries affected positively the all sectors via an increase in workers' wage.